Migrant Education, A Selected Bibliography (with ERIC Abstracts). ERIC CRESS Supplement No. 7. - ERIC Clearinghouse on Rural Education and Small Schools, Las Cruces, NM.; ERIC Clearinghouse on Rural Education and Small Schools ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
A supplement to seven previous bibliographies, this bibliography provides access to some of the latest resource material, research findings, and/or developments in migrant education. Part I contains 175 citations and abstracts which appeared in "Resources in Education" (RIE) from January 1976 through December 1976. Part II includes 14 citations of journal articles which appeared in "Current Index to Journals in Education" (CIJE) from January 1976 through December 1976. In addition to migrant education, the citations cover such topics as academic achievement, agribusiness, agricultural laborers, American Indians, ancillary services, bilingual education, child care, compensatory education programs, computer oriented programs, day care services, early childhood education, economic factors, educational assessment, educational programs, employment trends, English as a Second Language, family programs, Federal legislation, Federal programs, interstate programs, manpower utilization, Mexican Americans, migrant children, health services, housing, migrant workers, mobile educational services, parent participation, program effectiveness, Puerto Ricans, resource allocations, rural population, state programs, and tutorial programs. A combined RIE and CIJE subject index is provided. Ordering information and a list of the 16 ERIC clearinghouses are included. (NQ)
Availability: National Educational Laboratory Publishers, Inc., 813 Airport Boulevard, Austin, Texas 78702 (Stock No. EC-051, $8.00).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: 400-75-0025.
ERIC Note: For related document, see ED 118 292.
Educational level discussed: Early Childhood Education.
Educational level discussed: Elementary Secondary Education.
Keywords: Abstracts; Agricultural Laborers; Annotated Bibliographies; Bilingual Education; Day Care; Early Childhood Education; Educational Programs; Elementary Secondary Education; Employment Patterns; Federal Legislation; Health; Housing; Human Services; Mexican Americans; Migrant Education; Migrants; Mobile Educational Services; Outreach Programs; Parent Participation; Publications; Rural Population; Socioeconomic Influences; State Programs; Subject Index Terms; Tutorial Programs; Reference Materials, Bibliographies